Situation Analysis of Episiotomy in the Gulf: A Scoping Review - Zabidi, Faisal Zain Mohammed Al; Elsirafi, Maged Said; Muqresh, Mohamad Ayham; Ali, Mohamed Abdelghafour; Billah, Syed Muhammad Baqui (International Journal of Human and Health Sciences (IJHHS), 2021)
Objective: To assess episiotomy rates and indications in Gulf Council Countries (GCC). Materials and Methods: Two databases (PubMed, Google Scholar) were searched for relevant papers published from January 2014 to December 2019. Only 9 articles (3 in Saudi Arabia, 2 in Iraq and 1 in Oman, 1 in Qatar, 2 in UAE) were eligible. All articles reported episiotomy rates and indications as a primary or secondary outcome. Results: The cumulative rate of episiotomy in GCC was 52%, while this was 45% in Saudi Arabia. The Perineal tear reported rate in GCC was 29%, however, the cases accompanied with episiotomy was 65%. The most frequent indication was rigid perineum in both 16.9% in Saudi Arabia and 65.5% in Iraq. Conclusion: Episiotomy rates were reported to be high in GCC and Saudi Arabia. Only few articles reported episiotomy from the GCC. The commonly reported indications were both subjective for the doctor or the patient. We recommend that episiotomy rates with clear indications should be investigated in future research. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 286-291